Preliminary results on Macroalgae distribution in destructive processes - OSKOLSKAYA, O.I.; TORSKAYA, A.V.; TIMOFEEV, V.A. (Mediterranean Marine Science, 2001)
It has been shown, that the destruction of the coastal strip in region of action of Mikhailovsky landslide results in change of species structure and dominant species photophilous Cystoseira barbara on sciophylous Gracilaria verrucosa. In accordance with increasing sediments amount in sea water biomass and the morpho-functional parameters of the photophilous species are reducing, and at the sciophylous are growing. Progressing phenomenon of epiphytism is observed in algal populations in the southern part of researched region which is possible to consider as response reaction, leads to increase a synthesizing surface. Decreasing physiological activity is compensated by growth of the total surface of macrophytes. The increase of a sea water sediments leads to lowering ratio of long and shortwave pigments level of ATP-ase activity and raising concentration of the total sum of pigments in thalli.